The Long Kesh Hunger Strikers: 25 Years Later - Howard, Paul (Social justice, 2006)
The article focuses on the issue pertaining the hunger strike protest for Irish Republican prisoners to be granted political status at the Long Kesh Prison, in Northern Ireland. In this context, the author mentioned about Bobby Sands, Member of Parliament for Fermanagh and South Tyrone who died in the prison hospital of the H Blocks, Long Kesh Prison. As prisoners of war, Irish Republicans refused to accept the label criminal. But the British government had removed special category status for those sentenced for crimes related to the conflict after March 1, 1976. With this, the prisoner's five demands encompassed five political rights.